Design, preparation and in vitro characterizations of fluconazole loaded nanostructured lipid carriers - Amanda Velinna Fernandes; Chinna Raja Pydi; Ruchi Verma; Jobin Jose; Lalit Kumar (Universidade de São Paulo, 2020)
Present study was aimed to prepare and characterize fluconazole loaded nanostructured lipid carriers (FLZ-NLCs) for the treatment of fungal infections. Fungal infections are tremendously widespread and are the often faced dermatological condition worldwide. FLZ-NLCs was prepared by ultrasonication emulsion technique using stearic acid (SA) as solid lipid, castor oil as liquid lipid and tween 20 as a surfactant. The mean diameter of optimized FLZ-NLCs were found to be 359.15 ± 9.83 nm. The drug content and entrapment efficiency of NLCs was found to be 102.97 ± 7.45% and 87 ± 0.59%, respectively. In vitro drug release studies of FLZ-NLCs showed 37.34 ± 2.08% drug release over a period of 72 h. The above studies confirmed the prepared FLZ-NLCs may be useful for the treatment of fungal infections.